2013
DOI: 10.1371/journal.pone.0064730
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Particle Emitting 213Bi-Anti-EGFR Immunoconjugates Eradicate Tumor Cells Independent of Oxygenation

Abstract: Hypoxia is a central problem in tumor treatment because hypoxic cells are less sensitive to chemo- and radiotherapy than normoxic cells. Radioresistance of hypoxic tumor cells is due to reduced sensitivity towards low Linear Energy Transfer (LET) radiation. High LET α-emitters are thought to eradicate tumor cells independent of cellular oxygenation. Therefore, the aim of this study was to demonstrate that cell-bound α-particle emitting 213Bi immunoconjugates kill hypoxic and normoxic CAL33 tumor cells with ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 39 publications
2
39
0
1
Order By: Relevance
“…The limited range of α-particles (50–100 μm) confines their toxicity to a small radius from the site of the isotope decay, enabling more specific tumor killing capability without damage to the surrounding normal tissue; as opposed to β − -particles, which have a much longer range [26]. Furthermore the cytocidal effectiveness of α-particles has been shown to be independent of oxygen concentration [63], dose rate and cell cycle position [64]. Additionally, studies performed on a leukemia model indicated that α-emitter radionuclides exhibited cytotoxicity superior to that of β − -radiation or γ-radiation and are capable of killing cancer cells which are resistant to chemotherapeutic drugs such as doxorubicin [65].…”
Section: Resultsmentioning
confidence: 99%
“…The limited range of α-particles (50–100 μm) confines their toxicity to a small radius from the site of the isotope decay, enabling more specific tumor killing capability without damage to the surrounding normal tissue; as opposed to β − -particles, which have a much longer range [26]. Furthermore the cytocidal effectiveness of α-particles has been shown to be independent of oxygen concentration [63], dose rate and cell cycle position [64]. Additionally, studies performed on a leukemia model indicated that α-emitter radionuclides exhibited cytotoxicity superior to that of β − -radiation or γ-radiation and are capable of killing cancer cells which are resistant to chemotherapeutic drugs such as doxorubicin [65].…”
Section: Resultsmentioning
confidence: 99%
“…Their high effectiveness results from induction of lethal DNA double strand breaks. Cell survival studies have shown that in contrast to β − -radiation, α particle-killed cells independently of their oxygenation state, cell cycle position or fluency [124]. Due to these advantages, targeted α-particle therapy is the most rapidly developing field in nuclear medicine and radiopharmacy [125].…”
Section: α-Emitting Radionuclidesmentioning
confidence: 99%
“…However, a-particles present significantly higher energies than b-particles (4-9 MeV vs. 0.1-2.2 MeV), which combined with short path lengths results in high linear energy transfer and a greater probability of generating DNA double-strand breaks on interaction with cell nuclei. This occurs independently of tissue oxygenation, dose rate, and cellular resistance to photon irradiation and chemotherapy (1)(2)(3)(4)(5). Therefore, a-particles are highly cytotoxic and promising candidates for targeted radiotherapy.…”
mentioning
confidence: 99%